Optimizing the Power Take Off of a Wave Energy Converter with Regard to Wave Climate - Duclos, Gaëlle; Babarit, A.; Clement, A.H. (Journal of Offshore Mechanics and Arctic Engineering, 2006)
International audience Considered as a source of renewable energy, wave is a resource featuring high variability at all time scales. Furthermore wave climate also changes significantly from place to place. Wave energy converters are very often tuned to suit the more frequent significant wave period at the project site. In this paper we show that optimizing the device necessitates accounting for all possible wave conditions weighted by their annual occurrence frequency, as generally given by the classical wave climate scatter diagrams. A generic and very simple wave energy converter is considered here. It is shown how the optimal parameters can be different considering whether all wave conditions are accounted for or not, whether the device is controlled or not, whether the productive motion is limited or not. We also show how they depend on the area where the device is to be deployed, by applying the same method to three sites with very different wave climate.